Diseases Incidence and Severity of Sweet potato feathery mottle virus in Sweetpotato in Gianyar Regency, Bali - Ni Kadek Sudani Putri; Listihani Listihani; I Gusti Ayu Diah Yuniti; Putu Lasmi Yulianthi Sapanca; Farida Hanum; Ni Putu Pandawani; Dewa Gede Wiryangga Selangga (Agrovigor, 2023)
Sweet potato feathery mottle virus (SPFMV) (Potyvirus) was first discovered in Indonesia in 2018. No one has reported information about the incidence and severity of SPFMV disease. Therefore, this study aims to determine the incidence and severity of SPFMV in Gianyar, Bali. The research was carried out directly in the field with observational parameters such as symptoms, incidence and disease severity. Observations were made every week when the plants were 63 to 91 days after planting (DAP). The results showed that SPFMV causes purple ringspot symptoms. The incidence of the disease did not increase when the plants were aged 63 to 91 DAP, while the severity of the disease increased every week. The highest incidence and severity of the disease were 70% and 20.7%. The main cause of SPFMV infection in the field is probably due to the continuous use of stem cuttings from previous crops.